Sol. - Day, Phil, 1973-; Stamatellis, Phillip, 1968- (Hawthorn, VIC : ithoughtitoldyouguysiwasbusy, 2015)
Sol is a role-playing game in which players assume the roles of protagonists on the fictional planet of Sistere. At least one standard six-sided die is required for play. However, three six-sided dice are desirable.
Title from cover.
N copy accompanied by signed limited edition adjudicator's screen, number 100/100
Keywords: Fantasy games -- Handbooks, manuals etc; Fantasy games -- Rules; Role playing -- Handbooks, manuals, etc; Australian